Design and Analysis of Rectangular and Circular Microstrip Patch Antennas for 2.45 GHz ISM-Band Applications - Abdulkadir Abubakar; Aliyu Umar Abubakar; H. A. Abdulkareem; Jamilu Bala Hamza; Zahraddeen Lawan Sani (Darul Yasin Al Sys, 2026)
This paper presents the design, parametric analysis, and comparative evaluation of rectangular and circular microstrip patch antennas operating at 2.45 GHz in the industrial, scientific, and medical (ISM) band for wireless communication applications. Both antenna configurations were fabricated on a low-cost FR-4 dielectric substrate (εr = 4.5, thickness = 1.6 mm) to ensure compatibility with standard printed circuit board (PCB) manufacturing processes. The rectangular patch was designed with dimensions of 38.5 mm × 29.2 mm, while the circular patch had a radius of 16.42 mm; both were optimized using cavity-model formulations and closed-form analytical equations. A 50-Ω microstrip feed line with a width of 2.88 mm was employed for impedance matching. Comprehensive parametric studies were conducted to examine the influence of geometric parameters on resonance frequency, bandwidth, and radiation characteristics. The simulation results demonstrate that both antennas achieve satisfactory impedance matching, with S₁₁ < −10 dB at the target frequency. The rectangular configuration produces a directional radiation pattern suitable for point-to-point links, whereas the circular design provides near-omnidirectional coverage with potential for circular polarization. Comparative analysis against four recent literature designs indicates that the proposed antennas achieve competitive performance in terms of compactness, fabrication simplicity, and cost-effectiveness without requiring complex modifications such as slots or parasitic elements. The study concludes that rectangular and circular microstrip patch antennas fabricated on FR-4 substrates offer practical, low-profile, and integrable solutions for WLAN, IoT, and biomedical applications requiring compact and cost-effective antenna structures.